Balanced polymorphism fuels rapid selection in an invasive crab despite high gene flow and low genetic diversity. Issue 1 (13th September 2021) - Tepolt, Carolyn K.; Grosholz, Edwin D.; de Rivera, Catherine E.; Ruiz, Gregory M.
Abstract: Adaptation across environmental gradients has been demonstrated in numerous systems with extensive dispersal, despite high gene flow and consequently low genetic structure. The speed and mechanisms by which such adaptation occurs remain poorly resolved, but are critical to understanding species spread and persistence in a changing world. Here, we investigate these mechanisms in the European green crab Carcinus maenas, a globally distributed invader. We focus on a northwestern Pacific population that spread across >12 degrees of latitude in 10 years from a single source, following its introduction <35 years ago. Using six locations spanning >1500 km, we examine genetic structure using 9376 single nucleotide polymorphisms (SNPs). We find high connectivity among five locations, with significant structure between these locations and an enclosed lagoon with limited connectivity to the coast. Among the five highly connected locations, the only structure observed was a cline driven by a handful of SNPs strongly associated with latitude and winter temperature. These SNPs are almost exclusively found in a large cluster of genes in strong linkage disequilibrium that was previously identified as a candidate for cold tolerance adaptation in this species. This region may represent a balanced polymorphism that evolved to promote rapid adaptation in variable environments despite high gene flow, and which now contributes to successful invasion and spread in a novel environment. This research suggests an answer to the paradox of genetically depauperate yet successful invaders: populations may be able to adapt via a few variants of large effect despite low overall diversity. Abstract : see also the Perspective by Joshua A Thia.